Entrepreneurship Training and Capacity Building of Ghanaian Polytechnic Graduates - Azila-Gbettor, Edem M.; Harrison, Adjimah Paul (International Review of Management and Marketing, 2013)
This paper examines the suitability of the content and pedagogy of Ghanaian polytechnic syllabus in developing able and confident entrepreneur’s mindset of polytechnic graduates. Based on a survey of 750 final year students, the paper explores curriculum coverage of entrepreneurship syllabus, teaching and learning methods and emphasis and respondents capacity to start a business.The results indicated weaker link between the entrepreneurship development course of the polytechnic and preparedness of graduates to create businesses, at least from the student perspective which may be largely due to the teaching and learning methods. Keywords: Entrepreneur(ship); Education;Curriculum; Pedagogy; Content; Syllabus JEL Classifications: I12; L26